Prevalence of thrombocytopenia and its relation with WHO clinical and immunological staging among human immunodeficiency virus-infected children - Kumar, Durgesh; Kumar, Dinesh; Singh, Dharmendra Kumar; Rai, Ruchi (Indian Journal of Child Health, 2014)
Objective: The aim was to study the thrombocytopenia in human immunodeficiency virus (HIV) infected children and its relation with WHO clinical and immunological HIV/AIDS staging. Study Design: Observational analytic cross-sectional study. Materials and Methods: 47 ambulatory and clinically stable HIV-infected children (confirmed by enzyme-linked immunosorbent assay for HIV-1 and HIV-2) aged 18 months-18 years attending the out-patient Department of anti-retroviral therapy center at tertiary care setting, were included in this study. Detailed history was taken, and thorough clinical examination was done in all cases. Blood sample for complete blood count and CD4 count was taken. Primary Outcome: Thrombocytopenia in HIV-infected children. Secondary Outcome: WHO clinical and immunological HIV/AIDS staging in HIV-infected children and its relation to thrombocytopenia. Results: Of 47 studied children, thrombocytopenia was found in 14 (29.78%) cases. Patients with thrombocytopenia were found in all stages of the disease; however, it was strongly associated with increasing immunological stages (correlation coefficient, r = 0.948). Conclusion: Thrombocytopenia commonly occurs in children with HIV and its occurrence increases with an increase in WHO clinical and immunological HIV/AIDS staging.